Método de precificação baseada no custeio meta e custeio ABC aplicado em uma microempresa pecuarista - Cordeiro, Thiago Gondim (2012)
The pricing process is very important for a company to reach a satisfactory profitability. Many internal and external factors are crucial to this process, so a proper and systematic analysis of costs should be performed to detect distortions and support the decision-maker in several respects. This research aims to develop a methodology for efficient and effective pricing based on Activity Based Costing and Target Cost, so as to optimize the gains of small enterprises in the livestock industry. The paper is structured based on the theoretical framework, which an explanation of the pricing process is presented, also the importance and pricing methods. Also shown are the two costing systems used at work and their characteristics. Then the proposed method is described. The methodology included literature research and field research. The method was applied into a small ranching company and provided, like main results, the structure of the product cost for the adequacy of market price, the aware of the costs of the activities performed in the production process and points for improvement. The job application can guide entrepreneurs of the livestock sector to adequately manage their costs to become competitive in the market.